Assessment Formation of Open Data Sources During Their Aggregation For Analyzing Road Accidents - Sergey Savosin (FRUCT, 2021)
Analyzing data in a smart city often requires aggregating a large number of heterogeneous sources into a single system. For the selection of sources, it is necessary to first assess each source. This will provide informed data choices and improve the quality of decision making. The paper proposes a formalization of criteria for evaluating data and a method for evaluating a source based on the use of the proposed criteria. The performance of the method was evaluated by analyzing data on road accidents in St. Petersburg, Russia. Based on the analysis results, three data sources were selected, for which the analysis was carried out and the results were visualized.